A novel colonic drug delivery system of ibuprofen - Gohel, M C; Nagori, S A (Asian Journal of Pharmaceutics (AJP), 2014)
The present endeavor was directed towards fabrication of the novel colonic drug delivery system of ibuprofen. To begin with, the hydroxypropyl methylcellulose capsules containing adsorbate of eutectic mixture of ibuprofen and menthol and pregelatinized starch were coated with ethyl cellulose. These ethyl cellulose coated capsules were filled in another capsule and the capsules were coated with a EudragitÂ® S100. The in vitro drug release study was conducted using sequential dissolution technique at pH 1.2 (two hour), 6.0 (1hr), 7.2 (two hour) and 6.4 (three hour) mimicking different regions of gastrointestinal tract. The optimized batch with two per cent and 6.5% weight gain of ethyl cellulose and EudragitÂ® S100 showed less than eight per cent drug release in stomach and intestinal pH. The remaining 92% drug release was obtained thereafter from the optimized batch within two hours in colonic pH. Scanning electron microscopy study of the optimizedbatch confirmed presence of ibuprofen crystals (rod shape) in the formulation. The infrared spectroscopy study of the optimized batch indicated stability of ibuprofen during processing of the formulation.